Ethical Decision Making, Therapeutic Boundaries, and Communicating Using Online Technology and Cellular Phones - Yonan, Jesay; Bardick, Angela D.; Willment, Jo-Anne H. (Canadian Journal of Counselling and Psychotherapy, 2011)
Cellular telephones and social networking sites pose new challenges to the maintenance of therapeutic boundaries. One such difficulty is the possible development of dual relationships between clients and counselling professionals as a result of communicating by these means. Most regulatory bodies advise professional counsellors and psychologists to avoid engaging in dual relationships, but there are instances where they can be helpful or inevitable. The authors of this article discuss ethical concerns associated with using cell phones and online social networking sites to communicate with clients. Examples of ethical dilemmas involving recent technology are provided in order to help counselling professionals work through a decision-making process to manage the challenges that current technology poses to the therapeutic relationship. Recommendations for counselling professionals, future research, and formal training are provided.